In silico study and effects of BDMC33 on TNBS-Induced BMP gene expressions in zebrafish gut inflammation-Associated arthritis - Mostofa, Farhana; Yasid, Nur Adeela; Shamsi, Suhaili; Ahmad, Siti Aqlima; Mohd-Yusoff, Nur Fatihah; Abas, Faridah; Ahmad, Syahida (Multidisciplinary Digital Publishing Institute, 2022)
The bone morphogenic protein (BMP) family is a member of the TGF-beta superfamily and plays a crucial role during the onset of gut inflammation and arthritis diseases. Recent studies have reported a connection with the gut–joint axis; however, the genetic players are still less explored. Meanwhile, BDMC33 is a newly synthesized anti-inflammatory drug candidate. Therefore, in our present study, we analysed the genome-wide features of the BMP family as well as the role of BMP members in gut-associated arthritis in an inflammatory state and the ability of BDMC33 to attenuate this inflammation. Firstly, genome-wide analyses were performed on the BMP family in the zebrafish genome, employing several in silico techniques. Afterwards, the effects of curcumin analogues on BMP gene expression in zebrafish larvae induced with TNBS (0.78 mg/mL) were determined using real time-qPCR. A total of 38 identified BMP proteins were revealed to be clustered in five major clades and contain TGF beta and TGF beta pro peptide domains. Furthermore, BDMC33 suppressed the expression of four selected BMP genes in the TNBS-induced larvae, where the highest gene suppression was in the BMP2a gene (an eight-fold decrement), followed by BMP7b (four-fold decrement), BMP4 (four-fold decrement), and BMP6 (three-fold decrement). Therefore, this study reveals the role of BMPs in gut-associated arthritis and proves the ability of BDMC33 to act as a potential anti-inflammatory drug for suppressing TNBS-induced BMP genes in zebrafish larvae.